Evaluation of the effect of fluoride-containing luting cements on titanium and its effect on the shear bond strength - Kondumahanti V N. Avinash; Vahini Reddy; Jayakar Shetty; H C Nitin (Wolters Kluwer Medknow Publications, 2019)
Context: The most appropriate luting agent for titanium crowns is yet to be determined. Commonly used cements for luting titanium restorations give off leachable ions which may cause surface interaction with the titanium. Aims: The purpose of this study was to determine the shear bond strength of four grades of commercially pure titanium and Ti 6Al 4V with different cements and to examine for any surface physical changes. Settings and Design: The three luting cements, i.e., zinc polycarboxylate cement, glass ionomer cement, and zinc phosphate cement, were used to evaluate their effect on titanium. Ni Cr was used as a control. Methods and Material: The metal rods were milled to discs of 6 mm diameter and 4 mm height. Freshly extracted maxillary first molars, mounted in resin blocks, were sliced horizontally at occlusal third of the tooth. The discs were cemented to the sliced surface of the tooth with the three luting cements. The models were subjected to the shear bond strength test. Statistical analysis used: The data collected were analyzed statistically with one way ANOVA. A representative specimen of each group was observed under a scanning electron microscope. Results: The mean values ranged from 0.31 to 15.6 MPa. The shear bond strength values of the zinc polycarboxylate cement group were significantly high (P < 0.05). Corrosion of the titanium alloy luted with zinc polycarboxylate cement was observed. Conclusions: Cementation with zinc polycarboxylate cement provided high shear bond strength, but showed corrosion on titanium.